2016
DOI: 10.1016/j.enbuild.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Energy savings due to the use of PCM for relocatable lightweight buildings passive heating and cooling in different weather conditions

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
75
0
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(89 citation statements)
references
References 63 publications
1
75
0
13
Order By: Relevance
“…The building sector consumes 20-40% of all energy, especially in developed countries [1,3], and nearly 50% of the energy used in buildings is consumed by Heating Ventilation and Air Conditioning (HVAC) [3,4]. In addition, 30-40% of greenhouse gas emissions are caused by energy consumption in buildings [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…The building sector consumes 20-40% of all energy, especially in developed countries [1,3], and nearly 50% of the energy used in buildings is consumed by Heating Ventilation and Air Conditioning (HVAC) [3,4]. In addition, 30-40% of greenhouse gas emissions are caused by energy consumption in buildings [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Modern buildings consume 30-40% of the overall energy used all over the globe and experts predict this percentage will rise up to 50% by the year 2050 [1]. Due to such great energy consumption, buildings produce up to 30% of the greenhouse gases (GHG) released into the atmosphere every year, causing numerous problems around the world including global warming and climate change [2].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies on the above issues can be found e.g. in (Evola et al 2013;Izquierdo et al 2012;Marin et al 2016;Osterman et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After setting up these discs in stacks the holes form channels for the flow of the air. A ventilated external facade of the building containing PCM, was an object of extensive studies performed by de Gracia (2013de Gracia ( , 2016. A comprehensive review of the various configurations of the heat accumulators with PCMs for the use in buildings can be found in the paper (Rodriguez et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation